Resolusi Konflik antardesa di Kabupaten Kerinci, Jambi Conflict Resolution between Villages in Kerinci Regency, Jambi - Agung Iranda, Agung Iranda; Ramayanti, Rory (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
Research on conflict resolution has mainly focused on conflict resolution between nations, ethnicities, races, and regions. The study aims to explain the dynamics of conflict resolution between villages that often occur in Kerinci Regency. This study focuses on conflict resolution between villages of Pendung Talang Genting and Sleman. The study used a qualitative method with a phenomenological approach. The participants involved in the study were residents, village officials, and respected village elders. The results of the study revealed that conflict resolution was carried out through mediation, if a conflict cannot be resolved through mediation, legal action is then taken. Conflict resolution is also conducted using compensation and taking a softer line. Yet there are focus on the termination of conflict.